On a regular Ψ-fractional Sturm-Liouville problem - Ferreira, M. (2022)
In this short paper, we consider a $ψ$-fractional Sturm-Liouville eigenvalue problem by using left $ψ$-Caputo and right $ψ$-Riemann-Liouville fractional derivatives. We study the main properties of the eigenfunctions and the eigenvalues of the associated fractional boundary problem.